A mobile edge computing/software‐defined networking‐enabled architecture for vehicular networks. Issue 6 (8th July 2019) - Muthanna, Ammar; Shamilova, Regina; Ateya, Abdelhamied A.; Paramonov, Alexander; Hammoudeh, Mohammad
Abstract : This paper presents a system architecture to address the traffic density and the network coverage open research challenges in vehicular networks. This architecture adopts mobile edge computing (MEC) and software‐defined networking (SDN) technologies to increase the overall network reliability and scalability under high traffic density conditions. Then, a device‐to‐device (D2D) clustering method is described to provide network coverage for orphan nodes. The proposed architecture offers a reliable structure to support ultra‐low latency applications. Evaluation results using realistic conditions for various network scenarios show that the proposed MEC/SDN‐enabled vehicular network architecture achieves performance gains of up to 74% in terms of task blocking compared to its baseline implementation.